Aspek-Aspek Yang Berpengaruh Terhadap Kepatuhan Pajak UMKM Dilihat Dari Perspektif Ekonomi Dan Hukum Perpajakan. - Tresnawaty, Nia; Efrianto, Gatot (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
Tax compliance of Micro, Small, and Medium Enterprises (MSMEs) is a crucial factor in optimizing state revenue. This study analyzes aspects influencing MSME tax compliance from an economic and tax law perspective. Economically, factors such as income, financial literacy, and tax burden are key determinants. Meanwhile, from a tax law perspective, legal certainty, tax sanctions, and the quality of tax administration services play a role in shaping taxpayer compliance. This study employs a qualitative method with a descriptive-analytical approach, based on literature studies and secondary data. The findings indicate that MSME tax compliance is influenced by a combination of economic factors and prevailing tax regulations. Low tax literacy and regulatory complexity are major obstacles, whereas tax incentives and administrative simplifications can enhance compliance. Therefore, a more straightforward tax policy and comprehensive tax education are necessary to encourage MSMEs’ participation in the tax system more effectively.